Pipe up or clam up: the double-edged sword effect of perceived overqualification on employee voice behavior - Shuting Xiang; Dan Xiang; Jiahao Luo; Nuo Chen (Frontiers in Psychology)
Existing studies on the relationship between perceived overqualification (POQ) and voice behavior do not reach a consensus. Drawing on the job demands-resources model, this article explored the double-edged sword effect of POQ on voice behavior and its boundary condition. We test our hypotheses based on data collected from 430 employees across a three-wave study. The results demonstrate that POQ is negatively associated with employees’ voice behavior through emotional exhaustion. Conversely, it is also positively associated with voice behavior via self-efficacy. Employees’ careerism orientation careerism orientation moderates the relationship between POQ and self-efficacy, such that the effect is stronger when employees have high levels of careerism orientation.